The dilemma of institutional duality and multinational firms 1967-2017: Implications and future research. Issue 2 (18th May 2018) - Ahworegba, Akiebe Humphrey
Abstract : Purpose: The purpose of this paper is to improve the understanding of the dilemma of institutional duality (ID) confronting multinational corporations and to propose a workable solution for this problem. Design/methodology/approach: The author has searched the literature using several terms directly related to the dilemma of ID and multinational firms. Findings: The findings reveal that to attain "legitimacy", subsidiaries strive to balance institutional pressures stemming from external environments in the host country and their parent organizations. Understanding institutional theories of multinational corporations enables the subsidiaries to manage external pressures. ID impact varies among subsidiaries, depending on institutional contexts and internal strategies of subsidiaries. Originality/value: An "institutional duality incidence model" portraying how dual institutions make "legitimacy" problematic for subsidiaries is proposed. A framework for identifying factors generating ID dilemma and their management approach is also proposed. It is concluded that a multinational corporation that recognizes ID as a central concern is more likely to achieve and maintain a higher level of harmony with its subsidiaries and host countries.